In Vitro Selection of a Single-Stranded DNA Molecular Recognition Element Specific for Bromacil - Ryan M. Williams; Amanda R. Kulick; Srilakshmi Yedlapalli; Louisa Battistella; Cyrus J. Hajiran; Letha J. Sooter (Journal of Nucleic Acids)
Bromacil is a widely used herbicide that is known to contaminate environmental systems. Due to the hazards it presents and inefficient detection methods, it is necessary to create a rapid and efficient sensing device. Towards this end, we have utilized a stringent in vitro selection method to identify single-stranded DNA molecular recognition elements (MRE) specific for bromacil. We have identified one MRE with high affinity (Kd=9.6 nM) and specificity for bromacil compared to negative targets of selection and other pesticides. The selected ssDNA MRE will be useful as the sensing element in a field-deployable bromacil detection device.